2017
DOI: 10.22246/jikm.2017.38.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Review of Domestic Experimental Studies of Korean Medicine Treatment for Diabetes Mellitus Since 2013

Abstract: Objective: This study reviewed experimental studies on the effects of Korean medical treatment for diabetes mellitus (DM). Method: We reviewed 24 studies about DM that had been published since 2013. We searched the Korean Institute of Oriental Medicine (KIOM) database with the keyword '당뇨', '消渴', 'Diabetes'. Results:1. The studies used various Korean medicine treatments; 15 used single medicinal herbs, 6 used herbal complexes, and 2 used acupuncture.2. The measurement parameters used in the studies included bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
1
0
4
Order By: Relevance
“…消渴은 증상에 근거하여 병인이 되는 熱이 있는 장부에 따라 上消, 中消, 下 消로 구분하고 원인 장부에 대한 淸熱, 養陰하는 치료를 시행한다 4 . 그러나 당뇨병과 消渴이 완전히 일치하는 개념은 아니기에, 消渴의 한의학적 치료 를 당뇨병 환자에게 적용하기 위해서는 변증체계 의 확립 및 관련 연구가 필요하며, 협진의 효과 및 약물상호작용에 대한 연구가 이루어져야 한다는 점 이 지적되었다 5 . 이러한 맥락에서 한약재의 효과를 혈당 강하 기전을 밝히기 위하여, 인슐린 저항성, -세포 기능, 글루카곤유사펩타이드(glucagon-like peptide)-1 항상성 및 포도당(재)흡수를 조절하는 경로 등의 측면으로 실험 연구가 이루어지고 있다 6,7 , 임상 연구로는 당뇨병 전단계 피험자를 대상으로 한 산약추출물의 혈당조절 효과에 대한 무작위대 조임상연구가 진행된 바 있으며, 공복 혈당(fasting blood sugar, FBS)의 유의한 감소를 관찰하였다 8 13 .…”
Section: 이혜윤⋅정은선⋅윤영주⋅이상엽unclassified
See 1 more Smart Citation
“…消渴은 증상에 근거하여 병인이 되는 熱이 있는 장부에 따라 上消, 中消, 下 消로 구분하고 원인 장부에 대한 淸熱, 養陰하는 치료를 시행한다 4 . 그러나 당뇨병과 消渴이 완전히 일치하는 개념은 아니기에, 消渴의 한의학적 치료 를 당뇨병 환자에게 적용하기 위해서는 변증체계 의 확립 및 관련 연구가 필요하며, 협진의 효과 및 약물상호작용에 대한 연구가 이루어져야 한다는 점 이 지적되었다 5 . 이러한 맥락에서 한약재의 효과를 혈당 강하 기전을 밝히기 위하여, 인슐린 저항성, -세포 기능, 글루카곤유사펩타이드(glucagon-like peptide)-1 항상성 및 포도당(재)흡수를 조절하는 경로 등의 측면으로 실험 연구가 이루어지고 있다 6,7 , 임상 연구로는 당뇨병 전단계 피험자를 대상으로 한 산약추출물의 혈당조절 효과에 대한 무작위대 조임상연구가 진행된 바 있으며, 공복 혈당(fasting blood sugar, FBS)의 유의한 감소를 관찰하였다 8 13 .…”
Section: 이혜윤⋅정은선⋅윤영주⋅이상엽unclassified
“…枸杞子 역시 실험 연구에서 혈당과 지질을 감소시키는 효과가 있는 것으로 확인되었다5 . 아울 러 黃精과 같은 둥굴레 속 약재인 옥죽은 사포닌 을 통해 혈당을 강하시키고 과산화 조직 손상을 감소시킨다고 알려져 있다16 .兎絲子는 실험 연구에 서 경구 투여를 통해 공복혈당 감소, 중성 지방 감 소 및 체중과 면역 조직 증가 효과가 있음이 보고 되었으나, 인슐린 수준에 대한 명확한 효과는 밝혀 지지 않은 상태이다.…”
unclassified
“…[1] There have been studies on treatment methods in East Asian Traditional Medicine (EATM) for lowering blood sugar levels and its complications in patients with diabetes. Son et al [5] confirmed the antidiabetic effect of various herbal medicines, which suggested the possibility of expanding the field of EATM. Additionally, Jeong reported that fasting and postprandial blood glucose levels were improved by the administration of Jowiseunggi-tang, Dashiho-tang, Bojungikgi-tang, and Hoechunyanggyeok-san to patients with type 2 diabetes presenting with thirst and frequent urination.…”
Section: Introductionmentioning
confidence: 95%
“…초반에는 당뇨와 유사한 증상(渴而多飮, 消穀善 飢, 渴而尿數有膏油)을 공유하고 있는 개념인 消渴 을 중심으로 문헌적 고찰 연구가 진행되었고 17 , 점 차 본초 중심 연구로 발전하여 단미제로는 밀몽화 18 , 길경 19 , 목단피 20 , 금전초 21 , 포공영 22 , 맥문동 23 의 항 당뇨효과가 보고되었으며, 상백피와 오미자는 인슐 린 분비를 촉진하고, 목향, 상엽, 창출은 인슐린 저 항성 감소 효과가 있다고 알려졌다 24 . 복합제제 관 련해서는 대보음환 25 , 양격산화탕 26 , 황금탕 27…”
unclassified